Denitrogenation of diesel using ionic liquid characterization - Abdul Hadi, A Rahman (2014)
Diesel is widely used throughout the world on transportation mainly. But at the same time, environmental problem is increasing due to this kind of fuel. Diesel contain of several compounds like sulphur, nitrogen and so on. Nitrogen compounds for example indoles, carbazoles and pyridines can lead to health problem like coughing, shortness of breath and decreased lung function. Therefore, many researches have been done to discover how to eliminate this compound from diesel and one of them is the extraction of nitrogen compound from diesel using the ionic liquid. 3-methylimidazolium methylsulfate, ionic liquid is used in this research because of its unique properties in the extraction and synthesis process like excellent chemical and thermal stability and non-volatility for the process. This study conducts two steps of experiment. Ionic liquid is been analysed first using two method which are Fourier transform infrared spectroscopy (FTIR) and Carbon Hydrogen Nitrogen and Sulphur (CHNS) Analyser. By using Fourier transform infrared spectroscopy (FTIR), the spectrum result shows the ionic liquid has several functional groups such as alkene, aromatics and ketones according to the peaks of the graph. Based on the graph, the lowest peak is 626.46 cm-1 which can be aromatic or alkynes group. This group have C-H bond that exactly exist in the ionic liquid. While the highest peak the spectrum graph is 3126.60 cm-1 which can be carboxylic group. Meanwhile, the CHNS result shows the percentages of five major components in the ionic liquid, carbon 29.71%, hydrogen 5.46%, oxygen 33.75%, nitrogen 14.97%, and sulphur 16.11%. Those results are compared with the actual molecular formula of the ionic liquid to make sure the components are existed in the liquid. From the calculation from the CHNS analysis, the ratio of carbon is 4.9235, oxygen is 4.1988, nitrogen is 2.1274, hydrogen is 10.7826 and sulphur is 1.0000. The error is about 10% from the theoretical formula and it is acceptable